Impacts of livestock grazing on selected soil chemical properties in intensively managed pastures of Peninsular Malaysia - Ajorlo, Majid; Abdullah, Ramdzani; Mohd Hanif, Ahmad Husni; Abd Halim, Mohd Ridzwan; Yusoff, Mohd Kamil (Universiti Putra Malaysia Press, 2011)
This study investigates the impacts of short-term (1.5-year) heavy (SHG) and long-term (33-year) moderate (LMG) grazing intensities on the chemical properties of soil in the tropical pasture ecosystems. Two pastures with different grazing intensities and two ungrazed pastures were sampled at the varied depths of 0-10 and 10-20 cm in the Livestock Section of Universiti Putra Malaysia (UPM), Selangor, Malaysia. The EC and pH values in both the moderately and heavily grazed pastures were higher than the ungrazed ones. Meanwhile, the total carbon (TC) in the surface soil of the grazed pastures was 63% and 57% higher than the ungrazed pastures in the LMG and SHG pastures, respectively. The concentration of total nitrogen (TN) was not affected (P > 0.05) by livestock grazing. The concentration of available phosphorus (AP) in the surface soil and grazed pasture was significantly greater than the sub-surface soil and ungrazed pastures in the LMG pastures. The AP concentration in the grazed pasture and surface soil was 62.2% and 68.4% less than the ungrazed pasture and subsurface soil in the SHG pasture, respectively. It was found that the concentration of exchangeable cations (Ca+2, Mg+2, and K+) was affected by grazing. In particular, the concentration of exchangeable cations in both the moderately and heavily grazed pastures was also observed to be less than the ungrazed ones, except for Mg+2 in the LMG pasture. These results indicate that the impacts of livestock grazing on soil chemical properties were almost limited to the surface soil. After 33 years of moderate grazing, greater values were found for pH, EC, AP, and Mg+2 whereas lower values were stated for TN, TC, Ca+2, and K+. As compared to the ungrazed control, the concentrations of AP, TN, Ca+2, Mg+2, and K+ decreased after 1.5 years of heavy grazing.